New Policies in Renewable Energy and Their Impact on Rural Areas: The Case of Fier County, Albania - Hoti, Arlinda; (Dashi), Etleva Muca (Research Papers, 2025)
This study examines the impact of new renewable energy policies on rural areas in Albania, with a specific focus on Fier County. Through an analysis of solar energy projects developed during the 2018 – 2023, the study outlines the environmental and economic benefits for local communities. Investments in solar energy have improved access to clean and affordable energy, reducing dependency on fossil fuels and lowering carbon emissions. Another important aspect is that renewable energy brings sustainable development to rural areas by diversifying income sources for farmers. This helps stabilize the local economy, as farmers can benefit from energy production in addition to traditional agricultural activities. Renewable energy policies have created new economic opportunities for rural areas, through increased employment and improved energy infrastructure. The findings indicate that Albania is moving towards more sustainable development by promoting clean energy, significantly benefiting from the country’s natural resources. This transformation not only contributes to the environment but also strengthens rural communities and creates a solid foundation for future economic and social growth.